The Schorsing in Implementation of Administrative Decision that Endanger the Environment by Administrative Court - Miftah Sa'ad Caniago (Faculty of Law, Andalas University, 2018)
The postponement criteria of the implementation of KTUN (Administrative Court Decision) based on Article 67 of the Act Number 5, 1986 concerning the State Administrative Court (the Act of Administrative Court) merely states that such Postponement can be made if there is a very urgent circumstance which results in the plaintiff's interest to be lost if the sued state’s administrative decision is still implemented. By the promulgation of the Act Number 30, 2014 on the Governance Administration, it reregulates the delay of the implementation of the decision worded in Article 65. However, there are varies in the regulation of the implementation of the such decision pursuant to Article 67, of the Act Law Number 5, 1986 concerning the State Administrative Court. In accordance with Article 65 of the Administrative Governance Act, it rules more detailed regarding the reasons for the State Administrative Court that may delay the enforcement of a Government Decree, one of which if a Government Decision or Action